Prevalence of Spacing Malocclusion in Local Population Visiting a Dental College (Journal of Pharmaceutical Negative Results, 2022)
CONTEXT: Malocclusion can be defined as one in which the arches do not line up properly in any of the planes or one in which the position of the teeth deviates from the norm. Spacing in adults might been have inherited, acquired, or functional factors.OBJECTIVES: The purpose of this study is to determine the frequency of spacing in a particular South Indian community. MATERIALS AND METHODS: Data from patients who visited a private teaching hospital served as the basis for this investigation. By looking over medical records, data was gathered, and the data was then analysed.RESULTS AND DISCUSSION: According to the current study, between the ages of 21 and 40, there were more men (60.6%) than women (39.35%). In the younger adult age group, previous dental extraction (35.89 percent) was the most frequent cause of spacing (21-40 years). Males outnumbered females (81.74 percent) in the age range of 41 to 60. (18.26 percent ). It is clear that periodontitis (43 percent) accounted for the majority of spacing issues among adults (41-60 years). CONCLUSION: The study demonstrates the many etiologies of spacing in two various age groups. According to the data, patients between the ages of 21 and 60 most frequently had their teeth extracted for periodontitis and caries.